Cross-cultural Adaptation of the Adverse Childhood Experiences International Questionnaire - Flávia Garcia Pereira; Maria Carmen Viana (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To translate, adapt and validate the contents of the Adverse Childhood Experiences International Questionnaire to a Portuguese version, to be used in Brazil, named Questionário Internacional de Experiências Adversas na Infância. METHODS: This is a methodological study of cross-cultural adaptation of evaluation instruments presenting the results of semantic equivalence between the original instrument and the adapted version. The semantic equivalence of the instrument involved the following steps: 1) two translations and a synthesis of the translations; 2) two retranslations; 3) validation of contents by eight health workers; 4) synthesis of the retranslations; 5) pre-tests to assess acceptability, understanding and emotional impact of the questions; and, finally, 6) writing of the final version of the instrument. RESULTS: the adapted version proved to be easy to apply and to understand and achieved good semantic equivalence when compared to the original version. The psychometric properties of the instrument still need to be evaluated. Limitations and recommendations for improving the instrument and its use are presented. CONCLUSION: The process of cross-cultural adaptation of the Adverse Childhood Experiences International Questionnaire resulted in an adapted version to Brazilian Portuguese.